2015
DOI: 10.1073/pnas.1418445112
|View full text |Cite
|
Sign up to set email alerts
|

Absence of knots in known RNA structures

Abstract: The ongoing effort to detect and characterize physical entanglement in biopolymers has so far established that knots are present in many globular proteins and also, abound in viral DNA packaged inside bacteriophages. RNA molecules, however, have not yet been systematically screened for the occurrence of physical knots. We have accordingly undertaken the systematic profiling of the several thousand RNA structures present in the Protein Data Bank (PDB). The search identified no more than three deeply knotted RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 74 publications
1
39
1
1
Order By: Relevance
“…On the other hand, there are very few knotted RNA molecules -in a recent assessment [3] only three cases have been identified, but the corresponding structures are resolved poorly. Occurrence of knotted proteins is in between -several hundreds of knot-containing structure files and a dozen of truly independent structures [4,5,6,7] in the Protein Data Bank (PDB).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are very few knotted RNA molecules -in a recent assessment [3] only three cases have been identified, but the corresponding structures are resolved poorly. Occurrence of knotted proteins is in between -several hundreds of knot-containing structure files and a dozen of truly independent structures [4,5,6,7] in the Protein Data Bank (PDB).…”
Section: Introductionmentioning
confidence: 99%
“…[146] Es mag überraschen, dass natürlich verknotete RNA bisher noch nicht entdeckt wurde,die Gründe fürihr Fehlen sind unklar. [147] In bahnbrechenden Arbeiten von Seemans Gruppe wurden auch künstliche DNA-Knoten vorgestellt. [148] [149][150][151] Das erste Protein, in dem ein verknotetes Rückgrat identifiziert wurde,w ar eine a-Carboanhydrase.…”
Section: Knoten In Dnaunclassified
“…A survey showed that knotted RNA molecules are rare among currently known RNA structures [18]: Only 3 knotted RNA chains, with 3, 4 and 16 crossings, respectively, are found among 2,863 RNA structures contained in the PDB. However, conventional knot polynomials only consider phosphodiester bonds in an RNA molecule, and completely ignores the topological effects of hydrogen bonds in stem regions, the basis of the formation of RNA secondary structures.…”
Section: Introductionmentioning
confidence: 99%